Police response to same-sex intimate partner violence in the marriage equality era - Addington, Lynn A. (LGBTQ+ issues in criminology and criminal justice, 2024)
Growing research attention is being devoted to intimate partner violence (IPV) involving sexual minority individuals, which is providing insights about prevalence and disclosure patterns. While this work consistently finds that sexual minority IPV victims are reluctant to report to the police, little is known about actual police response to these victims. One unexplored area concerns how growing societal support and legal recognition of same-sex relationships might affect police response to IPV such as arrest. This issue is particularly timely given the U.S. Supreme Court’s 2015 decision in Obergefell v. Hodges that legalized same-sex marriage. The present study examines police response to IPV involving same-sex couples using arrest data from the National Incident-Based Reporting System (NIBRS). Findings indicate a relationship between legal recognition of same-sex marriage and arrest in IPV cases for both male and female same-sex couples. Implications of these findings for policy and future research are discussed.